A review of Cox's model extensions for multiple events - Abreu, Ana Maria; Sousa-Ferreira, Ivo (IJRDO-Journal of Applied Science, 2019)
In longitudinal studies, it is usual that a given subject can experience several failures. To analyse multiple failure-time data, we reviewed some extensions of Cox's regression model, which were proposed by: Prentice, Williams and Peterson (PWP); Andersen and Gill (AG); Wei, Lin e Weissfeld (WLW); and Lee, Wei and Amato (LWA). Our main goal is to underline the differences between these extensions, through a brief but careful description, providing also some guidance on how to choose the proper model for each situation. The guidelines presented in this work revealed to be a useful pointer to easily choose the most suitable model. Secondarily, we used the survsim and the survival R packages to illustrate the practical implementation of these models.